(untitled) - Eagan Press handbook (St. Paul. MN., 1999)
Emulsifiers is the seventh title in the Eagan Press Handbook Series. Combining a user-friendly format with expert guidance, handbooks in this series meet the needs of industry. Each title focuses on an ingredient or application, giving information that was previously unavailable in a single source and presenting its subject in straightforward language.
Keywords: Food industry and trade,Dairy products